2016
DOI: 10.1002/pc.24003
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of toughness and shear properties of multiwalled carbon nanotubes/epoxy composites

Abstract: In this work, Epocast 50-A1/946 epoxy have been modified with different weight percentages (0.25, 0.5, 0.75, 0.1, 1.25, and 1.5 wt%) of multiwalled carbon nanotubes (MWCNTs). Because of Epocast epoxy was primarily developed for joining and repairing of composite aircraft structural components, the optimum weight percentage of MWCNTs must be determined based on trade-offs between the optimum tensile, inplane shear and toughness properties of the developed MWCNTs-composites, which is the objective of this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…A sudden drop to zero-force was observed at the maximum contact force, demonstrating a brittle failure (fracture) of SAJs and provides a measurement of the displacement at maximum force. This behavior was attributed to the elastic-brittle behavior of either the bulk adhesive 3,40 or SAJs, [5][6][7] as shown in the tensile tests at RT. Moreover, the load-displacement curves of the CFRE laminates, in low-velocity impact tests, showed an elastic-brittle behavior at RT and 50 C. 33 Khashaba and Othman 33 have reported that the increasing of the test temperature from RT to 50 C has insignificant effects on the damage resistance of CFRE laminates under low-velocity impact loads.…”
Section: Load-displacement Curves Of Drop-weight Impact Testsmentioning
confidence: 93%
“…A sudden drop to zero-force was observed at the maximum contact force, demonstrating a brittle failure (fracture) of SAJs and provides a measurement of the displacement at maximum force. This behavior was attributed to the elastic-brittle behavior of either the bulk adhesive 3,40 or SAJs, [5][6][7] as shown in the tensile tests at RT. Moreover, the load-displacement curves of the CFRE laminates, in low-velocity impact tests, showed an elastic-brittle behavior at RT and 50 C. 33 Khashaba and Othman 33 have reported that the increasing of the test temperature from RT to 50 C has insignificant effects on the damage resistance of CFRE laminates under low-velocity impact loads.…”
Section: Load-displacement Curves Of Drop-weight Impact Testsmentioning
confidence: 93%
“…Hence, the specimen gauge region is under a state of constant shear force and pure shear stress (zero bending moment), which can be demonstrated by the shear-force and bending-moment diagrams of Iosipescu shear test specimen as illustrated elsewhere by Khashaba. 3,28
Figure 1.Experimental setup of the in-plane Iosipescu shear test.
Figure 2.(a) Dimensions of the double V-notches specimen, ASTM D5379, and (b) the instrumented specimens.
…”
Section: Experimental Workmentioning
confidence: 99%
“…Because MWCNTs have large aspect ratio (length/ diameter), they tend to aggregate and form bundles or ropes, usually with highly entangled network structure, which significantly limits their dispersion in the epoxy resin. Agglomerations of MWCNTs reduce the interfacial area in the nanocomposites, and hence reduce the opportunity to take the advantage of the unique properties of the MWCNTs [19] . Based on the extensive literature survey, a 0.5wt% MWCNTs was selected, which showed improvements in the mechanical properties for different epoxy systems by many researchers [2][3][4][5][6][7][8][9][10][11] .…”
Section: Determination the Mass Of Mwcnts And Epoxymentioning
confidence: 99%